2008
DOI: 10.1016/j.juro.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Gene MSH3 Polymorphism is Associated With the Risk of Sporadic Prostate Cancer

Abstract: Purpose-The mismatch repair (MMR) system is a DNA repair mechanism that corrects mispaired bases during DNA replication errors. Cancer cells deficient in the MMR proteins have a 10 2 -10 3 -fold increase in the mutation rate. Single nucleotide polymorphisms (SNPs) of MMR genes have been shown to cause a reduction in DNA repair activity. We hypothesized that mismatch repair gene polymorphism could be a risk factor for prostate cancer (PC) and that p53 Pro/Pro genotype carriers could influence MSH3 and MSH6 poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Several genetic polymorphisms are considered to be molecular markers that predict the risk, progression and prognosis of various cancers (3)(4)(5)(6)(7). Indeed, single nucleotide polymorphisms (SNPs) in several genes are reported to be associated with the risk of lung cancer (8)(9)(10), for example SNPs in the caspase-3 and vascular endothelial growth factor genes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic polymorphisms are considered to be molecular markers that predict the risk, progression and prognosis of various cancers (3)(4)(5)(6)(7). Indeed, single nucleotide polymorphisms (SNPs) in several genes are reported to be associated with the risk of lung cancer (8)(9)(10), for example SNPs in the caspase-3 and vascular endothelial growth factor genes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Vogelsang et al (2012) reported that the MSH3 rs26279 G/G versus A/A or G/A genotype was positively associated with esophageal cancer. Hirata et al (2008) found that the G/G or G/A genotype of the MSH3 rs26279 polymorphism might be a risk factor for sporadic prostate cancer. Moreover, the genetic variant of the MSH3 rs26279/MSH6 Gly39Glu -AA/ TC was associated with a decreased risk for breast cancer (Conde et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The association of MSH3 gene polymorphisms in ovarian cancer has also been reported, which suggests that MSH3 polymorphism may be a risk factor for ovarian cancer (Song et al, 2006). Hirata et al (2008) investigated MMR polymorphisms in sporadic prostate cancer. They found evidence for an increased risk of sporadic prostate cancer with single nucleotide polymorphisms (SNPs) in the MSH3 variants rs1805355 and rs26279.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to alterations that affect the function of single genes, mutations in some loci lead to alterations of multiple genes. While this concept has been best exemplified by defects in the mismatch repair genes that lead to increased genomic instability by accumulation of replicative errors in multiple genes [24,25], it is likely that altered mRNA processing, stability and translation also impact the function of many genes.…”
Section: Prostate Cancermentioning
confidence: 99%